Rodzinne i osobiste czynniki sprzyjające uzależnieniu młodzieży gimnazjalnej od mediów = Picture of teenagers at risk of becoming addicted to the media (or: factors encouraging the addiction of junior high school students to the media) - Miłkowska, Grażyna; Papiór, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The research runs in the school year 2011/2012 within the project "Life of the Lubuskie Region Inhabitants. Present and Prospects" proved that 1/4 of junior high school students from the Lubuskie Region are addicted to the media - mainly to the mobile phone, the Internet or the computer.
Keywords: młodzież gimnazjalna; uzależnienie od mediów; województwo lubuskie; badania